Analisis Sistem Antrian untuk Meningkatkan Pelayanan dan Kepuasan Pelanggan (Studi Kasus: Restoran Sedjagad 36) - Totok Hariyanto, Airlangga Putra; Herlina, Herlina (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT Alecta Global Investama is a company focused on the restaurant industry, operating two main locations in Surabaya, East Java. Its first restaurant is Alecta, while its second restaurant is Sedjagad. The company was founded by Mr. Sultan Fahad in 2020 and has its head office located on Jl. Ngagel Tim. No.36, Pucang Sewu, Gubeng District, Surabaya, East Java 60283.With a total of 30 employees, PT Alecta Global Investama offers various types of quality culinary to meet the tastes of customers in Surabaya. This research aims to simulate the customer queue system at PT Alecta Global Investama Restaurant to improve the efficiency of queues and the quality of service provided to customers. Long queues and unpredictable wait times often lead to customer dissatisfaction and decreased operational performance. Through the simulation approach of the queue system, this study analyzes the pattern of customer arrivals, dura Keywords: Queue system simulation, Queue efficiency, Restaurant, Service quality.